AUCTORITAS: AUTEUR ET AUTORITÉ CHEZ DIDEROT ( À PROPOS DE QUELQUES ÉPIGRAPHES ) - Stéphane Pujol (Studia Litterarum)
Diderot approaches the notions of work and author in a wide variety of ways. His works are “works” only because they “work” in the sense that they transform from within the categories of author and reader, blurring the boundaries between text and paratext, between center and periphery. The purpose of this article is to show that this deconstruction is deeply linked to Diderot’s conception of “literary” creation. This highlights the importance of the notion of threshold for Diderot, which means what precedes and surrounds a text, its margins. It is from this perspective that this article proposes to read some of Diderot’s epigraphs.